The impact of honors education on students’ academic and innovative achievements: a longitudinal study in China (2011–2021) - Yu, Jie; Tian, Dingyue; Wang, Zhuojun; Zhou, Yiyong (Frontiers in Education, 2024)
Honors education has ascended as an integral element within the sphere of global higher education, concentrating on fostering individuals who exhibit creativity and a history of innovative achievements. This focus has resulted in a marked increase in the enrollment of meticulously selected students. Despite its widespread adoption, there remains a scarcity of exhaustive longitudinal studies investigating its effects and associated variables. Regrettably, existing literature often neglects longitudinal examinations of the influence of honors programs beyond traditional academic measures. To address this shortcoming, this study deploys rigorous structural equation modeling (SEM) and linear regression analyses to meticulously examine a dataset comprising 319 students, who enrolled over a decade (2011)(2012)(2013)(2014)(2015)(2016)(2017)(2018)(2019)(2020)(2021) in a prestigious honors college at a preeminent university in China. The primary objective is to discern the predictive efficacy of Chinese honors education selection criteria on students' creative and academic accomplishments. This endeavor strives to clarify the complex interplay among students' creative personalities, academic performance, creative achievements, and standardized college entrance exam scores.Moreover, this research probes the enduring influences of elite student training models on collegiate innovative prowess. The findings emphasize that individuals who exhibit enhanced creative personality traits are predisposed to elevated levels of both innovation and academic attainment (β = 0.170, p = 0.017). Additionally, a significant inverse relationship is observed between general learning aptitude Honor's education 2 and subsequent academic performance (β= -0.008, p = 0.023), while students pursuing science disciplines demonstrate superior innovation outcomes compared to their liberal arts counterparts (β = 0.125, p = 0.048). Interestingly, neither gender nor general academic prowess exerts significant predictive power over collegiate innovation (β = -0.002, p = 0.134). These empirical insights equip policymakers and scholars with nuanced perspectives on the determinants shaping students' refined educational experiences, thereby inciting critical discourse concerning the refinement of selection criteria and the imperative of nurturing students' creative proclivities.